ANALISIS DETERMINAN KEJADIAN ISPA PADA BAYI DI KABUPATEN HULU SUNGAI SELATAN MENGGUNAKAN REGRESI LOGISTIK BINER - Nur Azmi Khairinda; Dewi Anggraini; Meitria Syahadatina Noor (Universitas Lambung Mangkurat, 2023)
The World Health Organization (WHO 2012) states that ISPA is the main disease that causes death in infants and occupies the first position in the number of illnesses in baby’s. Based on data from the South Kalimantan Provincial Health Office, Hulu Sungai Selatan District is the region with the highest infant mortality rate due to ISPA out of 13 districts/cities in South Kalimantan. This study aims to determine the factors that influence the incidence of ISPA in Hulu Sungai Selatan District using binary logistic regression analysis. Based on the results of binary logistic regression testing, it is known that nutritional status affects the incidence of ISPA in baby’s. Meanwhile, age, sex, immunization status and baby's weight at birth had no effect on the incidence of ISPA in baby’s in Hulu Sungai Selatan District. Therefore, there is a need for counseling for parents who have baby’s regarding protection from exposure to ISPA, especially for toddlers who are at risk of getting ARI, such as baby’s under one year old.Keywords: ISPA Incidence, Nutritional Status, Binary Logistic Regression